Digital capital and belonging in universities: quantifying social inequalities in the Philippines - Clamor, Wilfred Luis; Saloma, Czarina (Frontiers in Education, 2023)
This study examines social inequalities in Philippine universities that were exacerbated during the COVID-19 pandemic. A quantitative approach using a national sample of 677 university students was utilized to measure the mediating role of digital capital on social inequalities associated with belonging to academic spaces. For the purpose of determining direct and indirect impacts, structural equation modeling (SEM) was employed. Sociodemographic (i.e., gender, age, type of residence, and family income) and educational (i.e., type of university, year in the university, and excellence criterion) characteristics were the direct predictors that were examined as exogenous variables for both digital capital and belonging. Results indicate that type of residence (β=0.200, p<0.05), family income (β=0.220, p<0.001), and excellence criterion (β=0.271, p<0.01) are major determinants of digital capital. The model also shows that belonging is significantly predicted by age (β=0.087, p<0.05), family income (β=-0.207, p<0.001), and digital capital (β=0.576, p<0.001). Lastly, the findings reveal that the impacts of type of residence (β=0.116, p<0.05), family income (β=0.127, p<0.001), and excellence criterion (β=0.156, p<0.001) on belonging are successfully mediated by digital capital.